2017
DOI: 10.1007/s00330-017-4820-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the white matter impairments among ART-naïve HIV patients: a multivariate pattern analysis of DTI data

Abstract: • WM impairments along motor pathway were detected among the ART-naïve HIV patients • Prominent HIV-related WM impairments were observed in CC and frontal WM • The impairments of CC were significantly related to the HIV clinic statics • The CC might be susceptible to immune dysfunction and HIV replication • Multivariate pattern analysis had potential for studying the HIV-related white matter impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Variable results from DTI studies may be due, at least in part, to timing of evaluation relative to treatment (i.e., treatment naïve, currently un-medicated, chronically medicated, or older HIV infected individuals). For example, in early, treatment naïve HIV infection, white matter impairment (Tang et al, 2017 ) correlated with days since infection (Wright et al, 2015 ). In those on ART, a number of fiber tracts, including those of the corpus callosum and corona radiate are often reported as compromised (Leite et al, 2013 ; Xuan et al, 2013 ; Su et al, 2016 ; Wang et al, 2016 ).…”
Section: In Vivo Neuroimaging Of Hiv and Comorbiditiesmentioning
confidence: 99%
“…Variable results from DTI studies may be due, at least in part, to timing of evaluation relative to treatment (i.e., treatment naïve, currently un-medicated, chronically medicated, or older HIV infected individuals). For example, in early, treatment naïve HIV infection, white matter impairment (Tang et al, 2017 ) correlated with days since infection (Wright et al, 2015 ). In those on ART, a number of fiber tracts, including those of the corpus callosum and corona radiate are often reported as compromised (Leite et al, 2013 ; Xuan et al, 2013 ; Su et al, 2016 ; Wang et al, 2016 ).…”
Section: In Vivo Neuroimaging Of Hiv and Comorbiditiesmentioning
confidence: 99%
“…Compared with previous techniques that process medical images as pictures for visual inspection, radiomics introduces a new way to mine the information contained in medical images, and thus, radiomics offers an unprecedented opportunity for clinically assisted diagnosis. 17 Radiomics analysis has been successfully applied to produce imaging biomarkers for neuropsychiatric diseases such as Alzheimer disease, 18 human immunodeficiency virus-related neurodegeneration, 19 and bipolar disorder. Therefore, such studies have demonstrated the potential of radiomics in predicting hippocampal sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…For fMRI, the rst 10 time-point images were discarded for magnetization balance, after that, the remaining 230 time-point images were corrected and aligned to the rst time-point image to correct head movements; the resultant motion-corrected volumes were co-registered to the anatomical T1-weighted images and normalized to the Montreal Neurological Institute template, resampling to a 3 mm cube voxel resolution. For DTI, we employed the Eddy Correct tool to correct the head motion and eddy current distortions [38,39] , and used the Brain Extraction tool to remove the non-brain tissues of the B0 image and create the brain mask [40] , then we adopted the DTIFIT tool to t the diffusion tensor at each voxel and produced four parameter maps, encompassing fractional anisotropy, mean diffusivity, axial diffusivity and radial diffusivity [41] . For amyloid-PET, the structural images were individually registered to the averaged PET images, then we performed segmentation of all the co-registered structural images, spatially normalized the PET images to the Montreal Neurological Institute standard space by using the forward parameters (estimated during the segmentation), smoothed the images with an 8 mm full width at half maximum Gaussian kernel.…”
Section: Imaging Acquisition and Preprocessingmentioning
confidence: 99%